Bloch on Bloch on 'Religion - Bloch, Maurice (Religion and society, 2010)
The reflections presented here demonstrate the coherence and continuity of the part of my work that can be labeled as dealing with religion and ritual. This of course does not mean that everything I have written on the subject is coherent and continuous. Indeed as time has passed I have learned many things from my readings and experiences, from interacting with colleagues and friends, and from working with others, including the people I have studied and, above all, the PhD students I have supervised. As a result I have had to modify what I thought. Looking back I believe there is an ongoing line of argument in what I have published and this is what I attempt to clarify in what follows.